2010
DOI: 10.1007/s11886-010-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Repair: What the ACORN Trial Taught Us

Abstract: Progressive left ventricular remodeling is characterized by dilation of the left ventricle with a change in the heart from an elliptical shape to a more spherical shape. This change is part of the unfavorable natural history in patients with heart failure. The CorCap Cardiac Support Device (Acorn Cardiovascular, St. Paul, MN) is a mesh device that is implanted around the heart to reduce wall stress and the first therapy specifically designed to address left ventricular remodeling. The CorCap was studied in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A measure of effectiveness of an intervention treating secondary MR is reversing the disease of the ventricle, often measured through cardiac remodeling and LV geometry. As noted by the authors, other epicardial approaches have been previously described, including suture and mesh, 7 the Acorn epicardial wrap, 8 and the LV reshaping Coapsys device (Myocor, Inc, Maple Grove, Minn) in the RESTOR-MV (Randomized Evaluation of a Surgical Treatment for Off-Pump Repair of the Mitral Valve) trial. 9 The ACORN 8 and RESTOR-MV 9 trials demonstrated improved LV geometry, but no epicardial surgical technique has been widely adopted.…”
Section: And Mitra-fr (Multicentre Study Of Percutaneous Mitral Valve...mentioning
confidence: 99%
See 2 more Smart Citations
“…A measure of effectiveness of an intervention treating secondary MR is reversing the disease of the ventricle, often measured through cardiac remodeling and LV geometry. As noted by the authors, other epicardial approaches have been previously described, including suture and mesh, 7 the Acorn epicardial wrap, 8 and the LV reshaping Coapsys device (Myocor, Inc, Maple Grove, Minn) in the RESTOR-MV (Randomized Evaluation of a Surgical Treatment for Off-Pump Repair of the Mitral Valve) trial. 9 The ACORN 8 and RESTOR-MV 9 trials demonstrated improved LV geometry, but no epicardial surgical technique has been widely adopted.…”
Section: And Mitra-fr (Multicentre Study Of Percutaneous Mitral Valve...mentioning
confidence: 99%
“…As noted by the authors, other epicardial approaches have been previously described, including suture and mesh, 7 the Acorn epicardial wrap, 8 and the LV reshaping Coapsys device (Myocor, Inc, Maple Grove, Minn) in the RESTOR-MV (Randomized Evaluation of a Surgical Treatment for Off-Pump Repair of the Mitral Valve) trial. 9 The ACORN 8 and RESTOR-MV 9 trials demonstrated improved LV geometry, but no epicardial surgical technique has been widely adopted. Unlike other surgical and transcatheter devices addressing MR alone, the Mitral Touch is the latest example of an epicardial device that addresses both the secondary MR and the underlying diseased ventricle.…”
Section: And Mitra-fr (Multicentre Study Of Percutaneous Mitral Valve...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, percutaneous strategies as well as epicardial approaches have been developed with the aim of reducing mortality and morbidities, with controversial results. [7][8][9][10] The major limitation of these strategies is that they do not deal with the whole MV apparatus. Specifically, percutaneous treatments do not address LV geometry restoration, whereas epicardial approaches do not focus on annular dilatation.…”
mentioning
confidence: 99%